Climate-resilient strategies for wheat farming: minimizing climate impact, optimizing productivity, and maximizing profitability in the subtropical agroecological landscape of India - Meena, Vijay Singh; Jat, Raj Kumar; Durgude, Shubham; Kumar, Suneel; Sohane, R. K.; Jha, R. K.; Kumar, Abhay; Kumar, Ujjwal; Kumar, Anjani; Singh, R. N.; Reddy, Illathur R.; Pazhanismy, S.; et al. (Frontiers in Sustainable Food Systems, 2025)
This study builds upon existing knowledge to quantify the extent of on-farm yield gaps and identify the most effective climate-resilient strategies (CRSs) to bridge them. By addressing these objectives, the study seeks to enhance wheat yield and resilience in the adverse climatic conditions. Productivity and adoption of CRSs are key indicators to monitor the progress toward more resilient production systems. Total eight project hubs were identified across Bihar (Banka, Bhagalpur, Gaya, Khagaria, Madhubani, Munger, Nalanda, and Nawada) for farmers-field experiment-cum-demonstration during rabi season (2019–2020). Three climate-resilient technologies (i) zero tillage (ZT), (ii) raised bed (RB), and (iii) happy seeder (HS) were evaluated across varying planting times from November 13 to December 31. Field experiments-cum-demonstrations conducted across 566 hectares involving 980 farmers in eight districts of Bihar revealed that early wheat planting (13–30 November) significantly enhanced grain productivity (up to 4.96 t/ha) and profitability (net returns up to $863/ha, B:C ratio 1.92), while delayed sowing (post–mid-December) led to yield reductions of up to 57%. Among crop establishment methods, happy seeder (HS) and zero tillage (ZT) consistently outperformed conventional farmer-managed practices, achieving 12.6–14.5% higher net returns and benefit-cost ratios up to 2.02, underscoring the agronomic and economic advantages of timely planting and resource-conserving technologies. The study concludes that sowing wheat in the second week of November using the Happy Seeder (HS) significantly boosts productivity and profitability. These results offer robust evidence to refine regional planting advisories and promote climate-resilient practices for enhancing wheat adaptation across subtropical India.